Baseline incision characteristics and early scar maturation indices following cardiac device implantation. Issue 2 (19th January 2021) - Mehta, Nishaki Kiran; Morgaenko, Katerina; Haines, David; Rojas‐Pena, Edward; Heard, Brittney; Malhotra, Rohit; Darby, Andrew; Mangrum, James Michael; Mason, Pamela; Campbell, Christopher; Bilchick, Kenneth
Abstract: Aims: Dermatologic evaluation for cardiac implantable electronic devices (CIEDs) has not been established. We sought to ascertain baseline wound scar features using quantifiable surgical tools and scar scales on post‐CIED patients. Methods: A single‐center, prospective observational case‐control study was performed where 92 study subjects (40 healthy volunteers and 52 post‐CIED patients) completed the study. Durometer was used to quantify skin pliability before CIED placement, postprocedure, and 2 weeks postprocedure. Higher durometer readings signified reduced skin pliability. Durometer readings were compared to the patients' contralateral pectoral skin and to a healthy volunteer's cohort skin within the prepectoral region. Patient wounds were observed and graded using the Patient Observer Scar Assessment Scale (POSAS) and Manchester Scar Scale (MSS). Results: Baseline pectoral skin pliability readings were similar in healthy volunteers and CIED patient population. In comparison to preprocedural measurements, surgical site skin pliability decreased in postprocedural and 2 weeks follow‐up time points ( P ‐value .004 and <.001, respectively). The increases in durometer readings were higher in the older population (age >75 over time, P = .008). POSAS evaluations showed on average a thin painless hypopigmented scar with moderate stiffness. MSS scar evaluation showed a palpable scar with slight contour differences and color mismatch and appeared to be slightly better in the African American population. There was no difference in scar characteristics with preprocedural use of antiplatelet or anticoagulation or staple closure or gender. Conclusions: Serial measurements could be of value for development of new strategies for cosmesis and improved wound healing. Abstract : The skin pliability changes during early scar maturation following cardiac implantable electronic device implantation show a significant difference in the surgical and non‐surgical site at the 2 week follow‐up mark. Skin pliability was assessed with durometer readings (Shore Units) over the study duration.